Comprehensive conservative treatment for multiple metastases of skull osteosarcoma: A case report - Jiang, Dawei; Wang, Jingming; Chen, Qian; Wu, Junyi; Xu, Ming; Yu, Xiuchun (Frontiers in Neurology, 2023)
Background Skull osteosarcoma is relatively rare, and it is difficult to be diagnosed according to medical history and imaging examination due to the complex structure and diverse components of the brain. Consequently, there is only a limited number of patients who can undergo neoadjuvant chemotherapy before the operation. Although neoadjuvant chemotherapy plays an important role in the treatment of osteosarcoma, there is still a “bottleneck” in the current treatment method which when pulmonary metastasis occurs, or surgical treatment is not Enneking appropriate. Under such circumstances, the choice of treatment can be an issue. Case A 16-year-old male patient with multiple metastases of skull osteosarcoma was reported. The patient suffered not only tinnitus and hearing loss in the right ear but also right facial paralysis and headache. The preoperative brain MRI showed a tumor in the right cerebellopontine angle (CPA) area. He underwent skull tumor resection at another hospital in November 2018, during which process the biopsy revealed epithelioid osteoblastoma-like osteosarcoma. The patient had supplemental radiotherapy 1 month after surgery because of tumor recurrence. 32 months afterward, pulmonary metastases and multiple bone metastases were found. Then the patient underwent multiple conservative treatments which include Denosumab, Anlotinib, and DIA (cisplatin + ifosfamide + doxorubicin) chemotherapy at our hospital. After a series of 6 cycles of treatment, the patient can walk without aid. Lactate dehydrogenase (LDH) and Alkaline phosphatase (AKP) returned to a normal level. Fluorodeoxyglucose (FDG) metabolism in all bone metastases decreased to normal except for the ones in the proximal left femur, and the FDG metabolism in the left femur is significantly lower than that before treatment. Multiple bone metastases showed different extents of high-density calcification, and the volume of the local bone metastases has been reduced significantly. The patient‘s condition stayed stable at latest follow-up. Conclusion We found that multiple conservative treatments, which include Denosumab, Anlotinib and DIA chemotherapy, can improve patients' life quality, and help avoid further osteolytic destruction for patients with skull osteosarcoma and multiple metastases. Its specific mechanism and scope of the application still need to be further studied.